If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + -2x) = 7(x + -1) (1 * 4 + -2x * 4) = 7(x + -1) (4 + -8x) = 7(x + -1) Reorder the terms: 4 + -8x = 7(-1 + x) 4 + -8x = (-1 * 7 + x * 7) 4 + -8x = (-7 + 7x) Solving 4 + -8x = -7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 4 + -8x + -7x = -7 + 7x + -7x Combine like terms: -8x + -7x = -15x 4 + -15x = -7 + 7x + -7x Combine like terms: 7x + -7x = 0 4 + -15x = -7 + 0 4 + -15x = -7 Add '-4' to each side of the equation. 4 + -4 + -15x = -7 + -4 Combine like terms: 4 + -4 = 0 0 + -15x = -7 + -4 -15x = -7 + -4 Combine like terms: -7 + -4 = -11 -15x = -11 Divide each side by '-15'. x = 0.7333333333 Simplifying x = 0.7333333333
| 9x-(6x+9)=4x-30 | | 5+6n=8n+3 | | 4t-6=4-t | | (x)x(x+1)=506 | | 52-17=5(x-7) | | -3(t+5)=12 | | 3(y-2)=-6 | | 21=.5x(10+4) | | -2j^3d^5/-7j^5d^5 | | 4x=5/3 | | 2x+6x=3 | | 4x+40=12x+56 | | x^2-9/3=4x | | -x^2+10x=16 | | 5x+14=44 | | (x^2-9)/3=4x | | ((x^2)-9)/3=4x | | 15x-3=30x+2 | | 80x^2=70 | | 10x^2-22x-24= | | x=log[3](48) | | 20x^3+7x^2-6x= | | 27x^2-48x-64= | | z^2-25x^2+10x-1=0 | | s=-16t^2+535 | | a/20=10 | | 2y/4=3 | | (x+5)-6=6 | | x-16x-7y=1 | | 0.70x+0.15(30)=0.60(30+x) | | 8x/15=4/5 | | p+x=89 |